2008
DOI: 10.1002/ajmg.a.32419
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of the TCF4 gene in a girl with mental retardation but without the classical Pitt–Hopkins syndrome

Abstract: We have characterized a de novo balanced translocation t(18;20)(q21.1;q11.2) in a female patient with mild to moderate mental retardation (MR) and minor facial anomalies. Breakpoint-mapping by fluorescence in situ hybridization indicated that on chromosome 18, the basic helix-loop-helix transcription factor TCF4 gene is disrupted by the breakpoint. TCF4 plays a role in cell fate determination and differentiation. Only recently, mutations in this gene have been shown to result in Pitt-Hopkins syndrome (PHS), de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
82
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(84 citation statements)
references
References 20 publications
1
82
1
Order By: Relevance
“…Previous studies have provided clues that TCF4 may be a candidate gene for intelligence. For example, it was found that haploinsufficiency of TCF4 may induce PittHopkins syndrome that is characterized by severe mental retardation (Flora et al, 2007), and that mutations in the TCF4 gene are linked to other types of mental retardation, such as Pitt-Hopkins and Angelman syndromes (Kalscheuer et al, 2008;Takano et al, 2010). Quednow et al (2011) also found a moderate effect of rs9960767 on years of education in patients (although not in controls).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have provided clues that TCF4 may be a candidate gene for intelligence. For example, it was found that haploinsufficiency of TCF4 may induce PittHopkins syndrome that is characterized by severe mental retardation (Flora et al, 2007), and that mutations in the TCF4 gene are linked to other types of mental retardation, such as Pitt-Hopkins and Angelman syndromes (Kalscheuer et al, 2008;Takano et al, 2010). Quednow et al (2011) also found a moderate effect of rs9960767 on years of education in patients (although not in controls).…”
Section: Discussionmentioning
confidence: 99%
“…c Other mutations include a frameshift mutation creating a longer protein and a balanced translocation disrupting TCF4 but with a fusion transcript. 4,6 Phenotypic features reported by de Pontual et al 10 and some phenotypic features reported by Giurgea et al 8 were not attributed to specific patients. d Based on a Fisher exact two-tailed test, comparing missense mutations to the subtotal of those likely resulting in haploinsufficiency (the first two columns).…”
Section: Patient Ascertainmentmentioning
confidence: 92%
“…[2][3][4][5][6][7][8][9][10] A summary of the clinical features of these individuals, categorized by the type of mutation or deletion, is listed in Table 1. Figure 2 shows the locations of all reported mutations in TCF4.…”
Section: Review Of Cases With Tcf4 Mutations or Deletions In The Litementioning
confidence: 99%
“…A translocation that contains exon four of the TCF4 gene was also found to be associated with milder mental retardation when compared with patients with Pitt-Hopkins syndrome (20).…”
Section: Genementioning
confidence: 97%